2016
DOI: 10.1080/0886022x.2016.1184936
|View full text |Cite
|
Sign up to set email alerts
|

External dilator-assisted banding for high-flow hemodialysis arteriovenous fistula

Abstract: Creation of arteriovenous fistula (AVF) may lead to left ventricle hypertrophy and predispose for development or worsening of heart failure. It was postulated to reduce access blood flow if exceeded 2 L/min or cardiac index was higher than 3.0 L/min/m 2 . Numbers of techniques decreasing flow were described. The major disadvantage was the complexity of procedure and necessity of intraoperative flow measurement needed to establish desired flow. The technique of dilatorassisted banding with no endovascular cathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 16 publications
(22 reference statements)
0
18
0
Order By: Relevance
“…An alternative approach for access ligation is flow reduction. The banding procedure can be performed precisely using real-time flow ultrasound monitoring by means of a dowel, dilators, or balloons at various sizes [28][29][30]. Such procedures were shown to reduce effectively the symptoms of AVF-associated HF [28].…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach for access ligation is flow reduction. The banding procedure can be performed precisely using real-time flow ultrasound monitoring by means of a dowel, dilators, or balloons at various sizes [28][29][30]. Such procedures were shown to reduce effectively the symptoms of AVF-associated HF [28].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the modification of the cardiovascular risk through an intervention on AVF seems to be a promising intervention in KTx recipients, the patients were not convinced to a routine VA ligation (8). An alternative option could be a precision flow reduction by banding with a real-time access flow assessment or banding with the use of a sizing dowel (33)(34)(35). Using the data from the United States Renal Data Systems, it was found that AV access ligation was uncommon and performed in 4.6% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a high-flow hemodialysis fistula is associated with multiple adverse outcomes. These include steal syndrome [25], exotic complications such as hemothorax [26] or pulmonary embolism [27], and the impairment of cardiac function with high-output heart failure resulting from a large proportion a large proportion of the cardiac output recirculated through the enlarged fistulas [22,28,29]. While our working definition of CEF in our study was not harmonized to the diagnosis of ultrasonography-defined megafistula with high overall flow nor did we perform the Nicoladoni-Branham maneuver, our study entertains yet another striking possibility contributing to enlargement of arteriovenous accesses; the one of chronic salt-water overload.…”
Section: Discussionmentioning
confidence: 99%